Ribosomal protein L10(L12)(4) autoregulates expression of the Bacillus subtilis rplJL operon by a transcription attenuation mechanism - Yakhnin, Helen (Nucleic Acids Res, 2015)
Ribosomal protein genes are often controlled by autoregulatory mechanisms in which a protein encoded in the operon can either bind to newly synthesized rRNA during rapid growth or to a similar target in its mRNA during poor growth conditions. The rplJL operon encodes the ribosomal L10(L12)(4) complex. In Escherichia coli L10(L12)(4) represses its translation by binding to the rplJL leader transcript. We identified three RNA structures in the Bacillus subtilis rplJL leader transcript that function as an anti-antiterminator, antiterminator or intrinsic terminator. Expression studies with transcriptional and translational fusions indicated that L10(L12)(4) represses rplJL expression at the transcriptional level. RNA binding studies demonstrated that L10(L12)(4) stabilizes the anti-antiterminator structure, while in vitro transcription results indicated that L10(L12)(4) promotes termination. Disruption of anti-antiterminator, antiterminator or terminator function by competitor oligonucleotides in vitro and by mutations in vivo demonstrated that each structure functions as predicted. Thus, rplJL expression is regulated by an autogenous transcription attenuation mechanism in which L10(L12)(4) binding to the anti-antiterminator structure promotes termination. We also found that translation of a leader peptide increases rplJL expression, presumably by inhibiting Rho-dependent termination. Thus, the rplJL operon of B. subtilis is regulated by transcription attenuation and antitermination mechanisms.